Effect of Bypass Fat Supplementation on Productive and Reproductive Performance of Crossbred Cows - Sihag, Sajjan; Sihag, Z S; Kumar, Sushil; Dhaka, S S; Patil, C S (Indian Journal of Animal Nutrition, 2020)
Objective of this study was to examine the effects of dietary bypass fat supplementation on the productive and reproductive performance of lactating cattle. Eighteen lactating crossbred (Holstein Friesian x Haryana x Sahiwal) cattle yielding 14Â±2.0 kg milk per day and 10-15 days in milk were divided into three groups on the basis of milk yield and parity. Group T1 was fed control diet. Concentrate mixture in groupT2 was added with 2.15 % vegetable oil while that of T3 was supplemented with 2.5% bypass fat. Â The DMI was similar in all 3 groups. Digestibility of dry matter, ether extract and organic matter were significantly (P